Knowing God: Ibn ʿArabī and ʿAbd al-Razzāq al-Qāshānī's Metaphysics of the Divine - Lala, Ismail (Islamic Philosophy, Theology and Science. Texts and Studies, 2019)
Can we know God or does he reside beyond our ken? In Ibn ʿArabī and ʿAbd al-Razzāq al-Qāshānī's Metaphysics of the Divine , Ismail Lala conducts a forensic analysis of the nature of God and His interaction with creation. Looking mainly at the exegetical works of the influential mystic, Muḥyī al-Dīn ibn ʿArabī (d. 638/1240), and one of his chief disseminators, ʿAbd al-Razzāq al-Qāshānī (d. 736/1335?), Lala employs the term huwiyya , literally "He-ness," as an aperture into the metaphysical worldview of both mystics. Does Al-Qāshānī agree with Ibn ʿArabī's conception of God? Does he agree with Ibn ʿArabī on how God relates to us and how we relate to Him? Or is this where Sufi master and his disciple part ways?